2002
DOI: 10.1111/0952-1895.00197
|View full text |Cite
|
Sign up to set email alerts
|

Does Administrative Corporatism Promote Trust and Deliberation?

Abstract: How are policy processes affected by the fact that representatives of particular interests formally take part in public decision-making? This has been the central question in neocorporatist theory for several years. It is sometimes argued that corporatist does promote trust, public deliberation, and even the public interest. However, despite the theoretical focus on different modes of interest intermediation, how the causal mechanisms within corporatist arrangements actually work has been assumed, not empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 4 publications
(4 reference statements)
1
33
0
Order By: Relevance
“…Although such compromises should not be viewed as less noble than consensus achieved through deliberation (Mansbridge 2003), they clearly reflect the balance of forces, not the weight of arguments (Walzer 1999: 62). Strategic bargaining as opposed to persuasion or to argumentative problem solving (Scharpf 1991) is therefore also of relevance here 37 Oeberg's (2002Holzinger (2001a), using discourse analysis techniques, tests whether mediation procedures operate along deliberative lines or whether bargaining prevails.…”
Section: Research Questionsmentioning
confidence: 99%
“…Although such compromises should not be viewed as less noble than consensus achieved through deliberation (Mansbridge 2003), they clearly reflect the balance of forces, not the weight of arguments (Walzer 1999: 62). Strategic bargaining as opposed to persuasion or to argumentative problem solving (Scharpf 1991) is therefore also of relevance here 37 Oeberg's (2002Holzinger (2001a), using discourse analysis techniques, tests whether mediation procedures operate along deliberative lines or whether bargaining prevails.…”
Section: Research Questionsmentioning
confidence: 99%
“…There is a long tradition of corporatism in Sweden and it is sometimes claimed that it reached its peak in the 1970s and then waned to some extent in the 1990s, at least with regard to the formal representation of interest groups in governmental institutions (Ruin 1982;Micheletti 1991;Rothstein and Bergströ m 1999;BlomHansen 2000;Ö berg 2002). However, we have seen that the 1980 curriculum is not so vague, showing a clear inclination towards a moderate version of Critical Literacy without really excluding Personal Growth.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have suggested that corporatist arrangements may contribute to a national consensus between groups with opposing interests (Katzenstein 1985;Woldendorp 1995;Siaroff 1999;Ö berg 2002). By participating in public committees and boards they learn to appreciate the functions and operations of the state and become less inclined to react on the basis of ideological standpoints.…”
Section: Participation In the Corporatist System Of Political Decisiomentioning
confidence: 99%